2016
DOI: 10.1038/srep37020
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distributions in Hypertension Diagnosis, Measurement, Prevalence, Awareness, Treatment and Control Rates among Middle-aged and Older Adults in China

Abstract: Hypertension is of public health importance in China, but information on geographic distribution on hypertension by map visualization is limited for middle-aged and older adults. Regional geographic variations remain unexplained. Our study is to present geographic distributions at the provincial level and identify provinces and municipalities with high hypertension diagnosis, measurement and prevalence rates and/or low awareness, treatment, control rates among aged 45+ adults in China. We used data collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
7
22
3
1
Order By: Relevance
“…It was also found that the influencing factors for hypertension in our study were increasing age, gender, living in urban areas, overweight/obesity, physical inactivity, and family history of hypertension. This was partly consistent with many other previous studies [12,[14][15][16]. Our study also showed that highly educated people usually had a lower rate of hypertension than those with low education levels.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It was also found that the influencing factors for hypertension in our study were increasing age, gender, living in urban areas, overweight/obesity, physical inactivity, and family history of hypertension. This was partly consistent with many other previous studies [12,[14][15][16]. Our study also showed that highly educated people usually had a lower rate of hypertension than those with low education levels.…”
Section: Discussionsupporting
confidence: 82%
“…The awareness rate was nearly doubled compared with NNHS study, in which the overall awareness of hypertension was significantly greater for Method: enter: age, gender, region; forward-conditional: overweight/obesity, dyslipidemia, diabetes, physical inactivity, alcohol consumption, fruit consumption, personal history of stroke, personal history of coronary heart disease, family history of stroke, family history of coronary heart disease, family history of hypertension CI confidence interval, OR odds ratio women than for men 12]; however, the treatment rate was similar to that observed in our study. The awareness and treatment rates of hypertension in our present study were also higher than in many previous surveys such as the China Kadoorie Biobank Study [13] (30.5% awareness rate, 46.4% treatment rate) and the CHARLS survey conducted between June 2011 and March 2012 [15] (37.3% awareness rate, 21.1% treatment rate). The awareness rate in our survey was also relatively higher than the CCDRFS survey conducted from 2013 to 2014 16]; however, the treatment rate was lower than that observed in this study (31.9% awareness rate, 82.9% treatment rate).…”
Section: Discussioncontrasting
confidence: 50%
“…In the present study,oldersubjects and womenwere more likely to have hypertension, receive hypertension and T2DM treatment, and havetheir hypertensioncontrolled, which was consistent with previous studies [11,29].Older subjectscared for theirhypertension and T2DM more and were more likely to be coveredby medical insurance and have access to basic medical and public health services than younger adults [30,31]. It is reported that compared with men, womenaremore likely to visit doctors and receive timely treatment [32,33].Women are also more sensitive to antihypertensive drugsthan men and might bene tfrom the protective effects of estrogen [34].These factors may help explain why Chinese women have higher hypertension treatment and control rates than men.…”
Section: Discussionsupporting
confidence: 91%
“…In the past two decades, the pattern of global disease has changed considerably, from primarily communicable, maternal, and perinatal causes to non-communicable disease (NCD) [1,2]. According to the statistics of World Health Organization in 2012, 17.6 million people died of Cardiovascular disease (CVD) worldwide, and proportionally, this accounts for 31.43% of global mortality [3].…”
Section: Introductionmentioning
confidence: 99%